Investigating Individual Pre-trauma Susceptibility to a PTSD-Like Phenotype in Animals - Alexander, Khadijah S.; Nalloor, Rebecca; Bunting, Kristopher M.; Vazdarjanova, Almira (Frontiers in Systems Neuroscience, 2020)
Post-Traumatic Stress Disorder (PTSD) is a complex condition that develops after experiencing a severe emotional trauma, with or without physical trauma. There is no known cure and evidence-based treatments, which are effective in reducing symptoms, have low retention rates. It is therefore important, in addition to seeking new therapeutics, to identify ways to reduce the likelihood of developing PTSD. The fact that some, but not all, individuals exposed to the same traumatic event develop PTSD suggests that there is individual susceptibility. Investigating susceptibility and underlying factors will be better guided if there is a coherent framework for such investigations. In this review, we propose that susceptibility is a dynamic state that is comprised of susceptibility factors (before trauma) and sequalae factors (during or after trauma, but before PTSD diagnosis). We define key features of susceptibility and sequalae factors as: 1) they are detectable before trauma (susceptibility factors) or during/shortly after trauma (sequalae factors), 2) they can be manipulated, and 3) manipulation of these factors alters the likelihood of developing PTSD, thus affecting resilience. In this review we stress the importance of investigating susceptibility to PTSD with appropriate animal models, because prospective human studies are expensive and manipulation of susceptibility and sequalae factors for study purposes may not always be feasible. This review also provides a brief overview of a subset of animal models that study PTSD-related behaviors and related alterations in endocrine and brain systems that focus on individual differences, peri- and post-trauma. Attention is drawn to the RISP model (Revealing Individual Susceptibility to a PTSD-like Phenotype) which assesses susceptibility before trauma. Using the RISP model and expression of plasticity-associated immediate early genes, Arc and Homer1a, we have identified impaired hippocampal function as a potential susceptibility factor. We further discuss other putative susceptibility factors and approaches to mitigate them. We assert that this knowledge will guide successful strategies for interventions before, during or shortly after trauma that can decrease the probability of developing PTSD.